The impact of an educational programme on jordanian intensive care nurses' knowledge, attitudes, and practice regarding delirium and their levels of self-efficacy: A quasi-experimental design - Fadwa Alhalaiqa; Rami Masa'Deh; Omar Al Omari; Atef Shawashreh; Anas H Khalifeh; Richard Gray (Wolters Kluwer Medknow Publications, 2023)
Background: Delirium is a common problem among patients in Intensive Care Units (ICUs); however, it remains underdiagnosed. We aimed to determine the impact of a nursing education program on Jordanian nurses' knowledge, practice, attitudes, self-efficacy, and ability to detect delirium among ICU patients. Materials and Methods: We conducted a nonequivalent, quasi-experimental design from January 2019 to January 2020. A total of 175 nurses who work in an ICU were included at the baseline and divided into two groups: (1) intervention (86 nurses), who received education for 6 hours each day across two different days and (2) a control group (89 nurses), who maintained their usual routine of care. Data were collected by means of a booklet of questionnaires about the nurses' knowledge and practice, attitudes, and self-efficacy. Results: Data from 160 nurses were included in the analysis. The education program intervention (n = 81) significantly increased nurses' knowledge and practice, positive attitudes, and self-efficacy compared with the control group (n = 79, p < 0.001). In addition, nurses who received the educational intervention were able to detect more cases of delirium (28%, from a total of 51 patients) than the controls, who detected three (6.50%) out of a total of 31 patients (p = 0.003). Conclusions: The ICU nurses who received the delirium-focused educational program increased their knowledge and practice, positive attitudes, and their self-efficacy; in addition, their ability to detect delirium was increased. The implementation of such a program is recommended for the health policymakers and stakeholders.